Nilai Perjuangan Tokoh Utama Dalam Novel Sang Alkemis Karya Paulo Coelho: Pendekatan Semiotik Ferdinand De Saussure - Hikmah, Elok Faiqotul; Vardani, Eka Nova Ali; Susetyo, Agus Milu (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this study is to determine the values of struggle in the main character of the novel The Alchemist by Paulo Coelho using Ferdinand de Saussure's semiotic approach in the form of signifiers and signs. The method used in this research is a qualitative approach with descriptive method. The data used are paragraphs or dialogs in the novel The Alchemist by Paulo Coelho. Data collection techniques in this study are data reduction techniques, namely by selecting data by focusing on the data needed according to the criteria and data analysis is carried out by grouping data, coding data, interpreting and describing data. The results obtained show that the novel The Alchemist by Paulo Coelho contains the values of the struggle carried out by the main character. These values include (1) the value of struggle in the form of self-sacrifice totaling 2 data, (2) the value of struggle in the form of price-respect totaling one data, (3) the value of struggle in the form of patience and unyielding spirit totaling 6 data, and (4) the value of cooperation struggle totaling 2 data. From the data that have been found, it shows that Ferdinand de Saussure's semiotic approach can be used to analyze the values of struggle. This can be shown by the discovery of markers in the excerpts of the Alchemist's novel paragraphs that contain the markers of the values of struggle.